2006
DOI: 10.1038/sj.npp.1301203
|View full text |Cite
|
Sign up to set email alerts
|

Accumbal Neurons that are Activated during Cocaine Self-Administration are Spared from Inhibitory Effects of Repeated Cocaine Self-Administration

Abstract: Hypoactivity of the accumbens is induced by repeated cocaine exposure and is hypothesized to play a role in cocaine addiction. However, it is difficult to understand how a general hypoactivity of the accumbens, which facilitates multiple types of motivated behaviors, could contribute to the selective increase in drug-directed behavior that defines addiction. Electrophysiological recordings, made during sessions in which rats self-administer cocaine, show that most accumbal neurons that encode events related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 113 publications
(150 reference statements)
4
30
0
Order By: Relevance
“…The equations have been extensively used in behavioral self-administration (Ahmed and Koob, 2005;Samaha et al, 2002;Zernig et al, 2007), electrophysiological (Nicola and Deadwyler, 2000;Peoples and Cavanaugh, 2003;Peoples et al, 2004Peoples et al, , 2007, microdialysis (Wise et al, 1995), and voltammetric studies (Hermans et al, 2008;Stuber et al, 2005a, b), and a remarkable temporal relationship between modeled braincocaine concentration, NAc dopamine levels (Hermans et al, 2008;Shou et al, 2006;Wise et al, 1995), and cocaine-induced locomotor behavior (Shou et al, 2006) have been demonstrated. It is acknowledged that the relationship demonstrated here used modeled and not actual brain levels; nonetheless, the conclusions are based on relative changes in brain-cocaine concentrations and not the absolute magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…The equations have been extensively used in behavioral self-administration (Ahmed and Koob, 2005;Samaha et al, 2002;Zernig et al, 2007), electrophysiological (Nicola and Deadwyler, 2000;Peoples and Cavanaugh, 2003;Peoples et al, 2004Peoples et al, , 2007, microdialysis (Wise et al, 1995), and voltammetric studies (Hermans et al, 2008;Stuber et al, 2005a, b), and a remarkable temporal relationship between modeled braincocaine concentration, NAc dopamine levels (Hermans et al, 2008;Shou et al, 2006;Wise et al, 1995), and cocaine-induced locomotor behavior (Shou et al, 2006) have been demonstrated. It is acknowledged that the relationship demonstrated here used modeled and not actual brain levels; nonetheless, the conclusions are based on relative changes in brain-cocaine concentrations and not the absolute magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-cocaine concentrations were estimated using equations used by Pan et al (1991) ). This equation has been widely used to correlate estimated brain-cocaine levels with behavioral (Ahmed and Koob, 2005), electrophysiological (Peoples et al, 2004(Peoples et al, , 2007, microdialysis (Wise et al, 1995), and voltammetric measures (Stuber et al, 2005a,b;Hermans et al, 2008). Estimates in brain-cocaine levels in the literature are highly variable, spanning from the nanomolar to the micromolar range.…”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, use of this model has been widespread. Many self-administration studies have applied the equation to estimate brain concentrations of cocaine in live animals (Ahmed and Koob, 2005;Samaha et al, 2002;Zernig et al, 2007;Zimmer et al, 2011), and the equations have also been applied in studies using electrophysiology (Nicola and Deadwyler, 2000;Peoples and Cavanaugh, 2003;Peoples et al, 2004Peoples et al, , 2007, microdialysis (Wise et al, 1995) and voltammetry (Hermans et al, 2008;Stuber et al, 2005a, b). These studies have demonstrated that the modeled brain-cocaine concentrations are highly correlated with NAc dopamine levels (Hermans et al, 2008;Shou et al, 2006;Wise et al, 1995) as well as cocaine-induced locomotor behavior (Shou et al, 2006).…”
Section: Figurementioning
confidence: 99%